1986
DOI: 10.1080/00288306.1986.10427532
|View full text |Cite
|
Sign up to set email alerts
|

The calcalkaline White Hill Intrusive Suite, central Takitimu Mountains, western Southland, New Zealand

Abstract: The White Hill Intrusive Suite is a sequence of gabbroic to quartz dioritic subvolcanic intrusions within the Permian calcalkaline Takitimu Group. The suite is possibly the lateral and shallow level equivalent of the Longwood Complex and Mackay Intrusives, to the south and north, respectively. The intrusions are predominantly lensoid and concordant and show marked westward size and grain-size increases with increasing stratigraphic depth. The intrusives are characterised by simple mineralogy, dominated by plag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Cipriano (1986) demonstrated significant differences in the petrography and geochemistry of Drumduan and Brook Street basalts. Addition of the datasets of Houghton (1985Houghton ( ,1986) to Cipriano's (1986) data on Fig. 9, still supports these differences.…”
Section: Volcanic Clastssupporting
confidence: 58%
See 3 more Smart Citations
“…Cipriano (1986) demonstrated significant differences in the petrography and geochemistry of Drumduan and Brook Street basalts. Addition of the datasets of Houghton (1985Houghton ( ,1986) to Cipriano's (1986) data on Fig. 9, still supports these differences.…”
Section: Volcanic Clastssupporting
confidence: 58%
“…Kimbrough et al (1992) suggested that these intrusive complexes represent the roots of ankaramitic volcanic centres. In the Takitimu Mountains, the volcanic pile is intruded by gabbro-quartz diorite of the White Hill Intrusive Suite, and both are cut by hypabyssal dikes with hornblende K-Ar ages of 242-231 Ma (Houghton 1985(Houghton , 1986.…”
Section: Sources Of Conglomeratesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Brook Street Terrane (BST) is exposed throughout South Island, New Zealand, and represents a remnant of a Permian island-arc system. Comprehensive descriptions of the stratigraphy, paleontology, and sedimentology of the terrane have been published (Houghton 1981;Johnston & Stevens 1985;Houghton & Landis 1989;Landis et al 1999;Campbell 2000). In contrast, with the exception of early work by Sivell & Rankin (1983) and Houghton (1985), detailed petrological and geochemical analysis of the igneous rocks of the BST is limited.…”
Section: Introductionmentioning
confidence: 99%